Epidemiology of adolescent idiopathic scoliosis in Isfahan, Iran: A school-based study during 2014–2015 - Mohammadreza Etemadifar; Abdollah Hadi; Khalilollah Nazem; Meisam Abdar Esfahani; Ali Rabiei; Fereshte Taghvaee; Mahsa Mostajeran; Amin Nemati (Journal of Research in Medical Sciences, 2020)
Background: Scoliosis is a three-dimensional deformity of the spine with lateral curvature in addition to the rotation of vertebral bodies. The aim of the present study was to determine the prevalence of adolescent idiopathic scoliosis (AIS) in our society and its demographic-related factors. Materials and Methods: This was a cross-sectional study that took place from November 2014 to March 2015 in Isfahan, Iran. During the period of study, 24 schools were randomly chosen from six zones by a simple random sampling method. In each school, about 120 students were randomly selected and evaluated. Anterior forward bending test and scoliometry were done in all students and suspicious ones referred to Alzahra spine clinic for further evaluation. The diagnosis of AIS was based on radiographic finding and Cobb angle more than 10°. Data about age, sex, height, body mass index, hand dominancy, and type of schoolbag were recorded. Results: A total number of 3018 children were evaluated and 19 were diagnosed with AIS that showed the prevalence of 0.62%. None of the study variables had a significant relation with the presence of AIS. The cutoff point for the detection of AIS with scoliometry was calculated as 3.5, with a sensitivity of 73.7% and specificity of 86.7%. Conclusion: The prevalence of AIS in our area was 0.62%, which was lower than previous reports and did not have a relation with demographic factors; however, screening surveys identify a significant number of children with AIS who could benefit from preventive treatment.